Tinjauan Ekonomi Islam atas Perilaku Konsumen Muslim dalam Pembelian Produk UMKM: Studi Kasus pada RN Buket - Linda Puspita Sari; Mochamat Amarodin; Mohammad Saiful Rifai (Universitas Muhammadiyah Ponorogo, 2025)
This study examines Muslim consumer behavior in selecting and purchasing products from RN Buket MSME through the lens of Islamic economics. A qualitative descriptive approach was employed, with data collected through in-depth interviews with the business owner and 13 Muslim consumers. The findings reveal that consumer purchase decisions are shaped by a combination of rational, emotional, and religious considerations. Products are evaluated based on aesthetics, price, functionality, and alignment with Islamic values. The application of Sharia principles by the business owner, including ensuring product halalness, price transparency, and honesty in promotion, significantly influences consumer trust and satisfaction. Furthermore, the commitment to avoid riba, gharar, and maisir strengthens the MSME’s image as a trustworthy business adhering to Islamic economic principles. The trust cultivated fosters consumer loyalty, reflected in repeat purchases and product recommendations. Overall, implementing Islamic economic principles not only promotes blessings in business practices but also serves as an effective strategy for enhancing trust and loyalty among Muslim consumers toward MSME product.